2018
DOI: 10.3390/coatings8010031
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Properties of Fluoroacrylate-Modified Polysiloxane as a Fabric Coating Agent

Abstract: Polysiloxanes, which can add high softness and lubricity to treated textiles, have been proposed as softening post-finishing agents for fabric. However, the hydrophobicity of the finished fabric is not satisfactory. In this work, long-chain fluoroalkyl acrylate was used to modify the polysiloxane, aimed at improving hydrophobicity of the finished fabric and retaining its softness simultaneously. Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance spectra ( 1 H/ 13 C NMR), and thermograv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition, in the strong peaks at 0.7 and 2.0 ppm should be the characteristic absorption peaks of hydrogen atoms connected to CF in the fluorinated polysiloxane structure. This is basically consistent with the literature reports 23 …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, in the strong peaks at 0.7 and 2.0 ppm should be the characteristic absorption peaks of hydrogen atoms connected to CF in the fluorinated polysiloxane structure. This is basically consistent with the literature reports 23 …”
Section: Resultssupporting
confidence: 94%
“…This is basically consistent with the literature reports. 23 1 H NMR (CDCl 3 , 400 MHz) δ ppm: 5.90-6.05, 5.74- polysiloxane on the conversion and coagulation. It can be seen that as the vinyl content of fluorinated polysiloxane decreases and the molecular weight increases, the monomer conversion gradually decreases and the coagulation increases.…”
Section: Characterization Of Fluorinated Polysiloxanesmentioning
confidence: 99%
“…Therefore, a higher-resolution instrument was required. The AFM is a new instrument for measuring the fine morphology of polymer films at nanoscale and is often encountered in recent publications [18][19][20][21]. So, in this study we also used silicon wafer as the simulated fiber matrix to study the fine morphology of the PFAS-SiO 2 -3 film by AFM, and the results are shown in Figure 5.…”
Section: Afm Observationmentioning
confidence: 99%
“…Commercially‐available products of polysiloxanes possessing reactive groups for further crosslinking and modification reactions have been widely use. Modified and functional polysiloxanes are also reported in literature 1–6 with incorporation of other functional moieties to the structures of polysiloxanes.…”
Section: Introductionmentioning
confidence: 99%
“…Commerciallyavailable products of polysiloxanes possessing reactive groups for further crosslinking and modification reactions have been widely use. Modified and functional polysiloxanes are also reported in literature [1][2][3][4][5][6] with incorporation of other functional moieties to the structures of polysiloxanes. cD 4 compounds possessing reactive groups could be considered as effective units for building up polymeric materials, since chemical reactions could be performed at the reactive groups of the cD 4 compounds to result in functional cD 4 analogues.…”
Section: Introductionmentioning
confidence: 99%